Balloon-Assisted Corpus Callosotomy. Reducing the Impact of Transcallosal Approaches. Issue 3 (18th March 2023) - Paolini, Sergio; Severino, Rocco; Ciavarro, Marco; Missori, Paolo; Cardarelli, Giovanni; Mancarella, Cristina
Abstract : BACKGROUND: The interhemispheric transcallosal approach is widely used to remove intraventricular lesions. Corpus callosotomy gives immediate access to the ventricular chambers but is invasive in nature. Loss of callosal fibers, although normally tolerate, may cause disturbances ranging from a classical disconnection syndrome up to minor neuropsychological changes. OBJECTIVE: To open an operative window in the corpus callosum through separation rather than disconnection of the white matter fibers. METHODS: In 7 patients undergoing the interhemispheric transcallosal approach for intraventricular lesions, lying around or below the foramen of Monro, a stoma was created within the corpus callosum by using a 4F Fogarty catheter. The series included 3 colloid of the third ventricle, 2 thalamic cavernomas, 1 subependymoma, and 1 ependymoma of the foramen of Monro. We illustrate the technique and the clinico-radiological outcome, focusing on the size of callosotomy as seen on postoperative MRI. RESULTS: The balloon-assisted corpus callosotomy provided a circular, smooth-walled access to the ventricular chambers, which allowed uncomplicated removal of the lesions. On postoperative MRI, the size of the callosotomy shrinked compared with surgery (2.8-6.4 mm at follow-up vs 6-9 mm as measured intraoperatively). No signs of disconnection syndrome or new permanent deficits were observed in this series. CONCLUSION: The balloon-assisted technique produces a small callosotomy, without clinical consequences, showing a self-closing trend on postoperative MRI. This technique is a rewarding tool to reduce the impact of callosotomy while keeping the advantages of microsurgical interhemispheric approaches.